Politics of civil wars conflict, intervention and resolution - Misra, Amalendu (Routledge, 2008)
Civil war is one of the critical issues of our time. Although intrastate in nature, it has a disproportionate and overwhelming effect on the overall peace and stability of contemporary international society. This book investigates why civil wars have become so widespread and how can they be contained?